PARTICIPATORY SEMINAR ON THE STUDY OF "4BLOCKS": DESIGN AND RESULTS (City: History, Culture, Society, 2020)
In this report, we highlight the key results from the field research seminar on an unconventional housing project builtin the late 1980s. 4blocks on Podil is an under-researched urban space of late socialism in the Podil area in Kyiv,although the discussion about its value and significance is ongoing. To tackle this issue we developed an integratedapproach and placed an emphasis on the voices of citizens that could provide a basis for the re-evaluation of architecturein the future. Participants of the seminar conducted interviews with locals and assessed critical papersconcerning the built project to find preliminary answers to the questions concerning the role of the author, quality,and symbolism of the environment and ability of buildings to withstand time. We comment on the possibilities of themethod as well as shed light on the key difficulties social scientists could face while utilizing it to research urbanspaces elsewhere.
Keywords: 4blocks; Kyiv; Podil; housing.